Using Non-Immersive Virtual Reality to Teach Life Skills to Students With Disabilities in Rural Schools. - Norwine, Laura; Bouck, Emily; Reiley, Sarah; Long, Holly M.; Jakubow, Larissa; Nuse, James (Rural Special Education Quarterly, 2025)
Students with disabilities may find it difficult to learn and gain the life skills needed to live, work, socialize, and attend postsecondary education. In vivo and community-based instruction (CBI) are among the most effective ways to teach life skills, especially with a goal of generalization. Despite the strong relationships that often exist in rural locales between schools and the broader community, students may not be able to access effective instructional practices. Technology-based options, such as virtual reality (VR), offer effective alternatives. Using a multiple probe single-case research design, researchers examined the efficacy of non-immersive VR to provide instruction in targeted life skills to three students with disabilities attending a rural U.S. school district. The researchers found two main results: (a) a functional relation between the independent variable—the non-immersive VR—and the dependent variable of student accuracy on the task analysis steps of the targeted life skill, and (b) students maintained high levels of accuracy in completing the task analysis steps post-intervention (i.e., independent variable removed).